(Dis)Regarding the Caregivers: The Neglect of Migrant Women in Care and Paid Domestic Work in Costa Rica - Gatica López, Gustavo Adolfo (2026)
In Costa Rica, there is a slight feminization of migration. The main occupation for foreign women is Paid Domestic Work (PDW), which includes care work as defined in the Labor Code. The social integration of immigrant women is contingent upon formal aspects, particularly immigration regularization, as well as historical and structural factors, and the existence of support networks. This article seeks to answer the question: What are the working conditions of foreign women employed in PDW and care work? The evidence reveals unfavorable working conditions and a lack of care from society towards this group of workers.